Predictive value of CHA2DS2-VASc score in radial artery occlusion after transradial coronary angiography - Nadir, Aydın; AY, Nuray Kahraman (Frontiers in Cardiovascular Medicine, 2023)
Background Radial artery occlusion is the most common complication of transradial catheterization. RAO is characterized by thrombus formation due to catheterization and endothelial damage. CHA2DS2-VASc scores are the current scoring systems used to determine the risk of thromboembolism in patients with atrial fibrillation. The aim of this study was to investigate the relationship of CHA2DS2-VASc score with radial artery occlusion. Methods This prospectively designed study was included 500 consecutive patients who underwent coronary artery transradial catheterization for diagnostic or interventional procedures. The diagnosis of radial artery occlusion was made by palpation examination and Doppler ultrasound at the twenty-fourth hour after the procedure. Independent predictors of radial artery occlusion were determined by logistic regression analysis. Results Radial artery occlusion was observed at a rate of 9%. The CHA2DS2-VASc score was higher in the group of the patients who developed radial artery occlusion (p < 0.001). Arterial spasm (OR: 2.76, 95% CI 1.18–6.45, p: 0.01), catheterization time (OR: 1.03, 95% CI 1.005–1.057, p: 0.01) and CHA2DS2-VASc score ≥ 3 (OR: 1.44, 95% CI 1.17–1.78, p: 0.00) as significant independent predictors of radial artery occlusion. A high CHA2DS2-VASc score was associated with the continuity of the occlusion after the treatment (OR:1.37, 95% CI 1.01–1.85, p: 0.03). Conclusions An easily applicable CHA2DS2-VASc score of ≥3 has a predictive value for radial artery occlusion.